Cysteine sulfinic acid decarboxylase regulation: A role for farnesoid X receptor and small heterodimer partner in murine hepatic taurine metabolism. Issue 10 (18th October 2013) - Kerr, Thomas A.; Matsumoto, Yuri; Matsumoto, Hitoshi; Xie, Yan; Hirschberger, Lawrence L.; Stipanuk, Martha H.; Anakk, Sayeepriyadarshini; Moore, David D.; Watanabe, Mitsuhiro; Kennedy, Susan; Davidson, Nicholas O.
<x xml:space="preserve">Abstract</x> Aim Bile acid synthesis is regulated by nuclear receptors including farnesoid X receptor (FXR) and small heterodimer partner (SHP), and by fibroblast growth factor 15/19 (FGF15/19). We hypothesized that hepatic cysteine sulfinic acid decarboxylase (CSAD) (a key enzyme in taurine synthesis) is regulated by bile acids (BA). The aim of this study was to investigate CSAD regulation by BA dependent regulatory mechanisms. Methods Mice were fed a control diet or a diet supplemented with either 0.5% cholate or 2% cholestyramine. To study BA dependent pathways, we utilized GW4064 (FXR agonist), FGF19 or T‐0901317 (liver X receptor [LXR] agonist) and Shp−/− mice. Tissue mRNA was determined by quantitative reverse transcription polymerase chain reaction. Amino acids were measured by high‐performance liquid chromatography. Results Mice supplemented with dietary cholate exhibited reduced hepatic CSAD mRNA while those receiving cholestyramine exhibited increased mRNA. Activation of FXR suppressed CSAD mRNA expression whereas CSAD expression was increased in Shp−/− mice. Hepatic hypotaurine concentration (the product of CSAD) was higher in Shp−/− mice with a corresponding increase in serum taurine conjugated BA. FGF19 administration suppressed hepatic cholesterol 7‐α‐hydroxylase (CYP7A1) mRNA but did not change CSAD mRNA expression. LXR activation induced CYP7A1 mRNA yet failed to induce CSAD mRNA expression. Conclusion BA regulate CSAD mRNA expression in a feedback fashion via mechanisms involving SHP and FXR but not FGF15/19 or LXR. These findings implicate BA as regulators of CSAD mRNA via mechanisms shared with CYP7A1.